Neuromuscular diseases in intensive care - Yahya Lahrichi; Ghita Mninou; Ali Derkaoui; Ibrahim Bechri; Abdelkrim Shimi; Mohammed Khatouf (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2023)
Guillain-Barre syndrome and myasthenia gravis are common in the Intensive Care Unit (ICU) and are not always easy to diagnose in the emergency department. The short-term risk is the occurrence of respiratory muscle paralysis, which must be monitored by repeated measurement of vital capacity, and the existence of respiratory impairment requires transfer to intensive care. Apart from specific therapeutic options (plasma exchange, intravenous immunoglobulins and anticholinesterase agents), management is mainly symptomatic. Our work is a retrospective study, concerning 23 cases of neuromuscular diseases in the ICU from a period from 2018 to 2022. The various epidemiological, clinical, paraclinical, therapeutic, and evolutionary data were collected from the files of the Intensive Care Department A1 of the Hassan II University Hospital of Fez for the study. Osteomas of the paranasal sinuses are benign, often asymptomatic, tumors that progress very slowly. Endocranial development of an osteoma can breach the dura mata, allowing air to enter the cranium producing pneumocephalia which leads to severe neurological deficiencies. Pneumocephalia is an exceptional complication of osteoma.